The Relationship of Breathing and COVID-19 Anxiety When Using Smart Watches for Guided Respiration Practice: A Cross-Sectional Study - Wu, Yu-Feng; Chen, Mei-Yen; Ye, Jian-Hong; Hong, Jon-Chao; Ye, Jhen-Ni; Wu, Yu-Tai (Frontiers in Psychology, 2022)
COVID-19 mortality rates are increasing worldwide, which has led to many highly restrictive precautionary measures and a strong sense of anxiety about the outbreak for many people around the world. There is thus an increasing concern about COVID-19 anxiety, resulting in recommending approaches for effective self-care. From a positive psychology perspective, it is also important for people to have positive affect when dealing with this pandemic. According to previous literature, respiration is considered to be an effective way to enhance people’s mental health. Among all the wearable devices, Apple Watch has the largest market share, so this study recruited Chinese users that use respiration exercise function on Apple Watch; a total of 316 valid data were retrieved. Meanwhile, to understand one approach related to using Apple Watch to practice respiration to reduce COVID-19 anxiety about being infected during the COVID-19 outbreak, this study used a web-based cross-sectional survey to examine anxiety about being infected by COVID-19 among Chinese people who had been using the Apple Watch to practice respiration during the period of the COVID-19 outbreak. The study was based on the Health Theoretical Model, and the model was developed with four dimensions and was validated with structural equation modeling. The results of this study showed that practicing few minutes had a positive relationship on positive attitude, and positive attitude had a negative relationship on pandemic anxiety and a positive relationship on continuance use intention. Anxiety about the pandemic had a negative relationship on the intention to continue using the function. This showed that respiration practice can help to suppress the increase in anxiety levels regarding this pandemic.